ENHANCING SOCIAL COHESION: A STRATEGIC FRAMEWORK FOR THE DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP THROUGH THE PARTICIPATORY MODEL - Anna Verbytska; Alona Revko (Baltic Journal of Economic Studies)
The purpose of the article is to formulate a strategic framework that emphasises the interdependence between social cohesion and social entrepreneurship as a tool for reintegrating servicemen, veterans and their families based on an assessment of the level of social cohesion in the local hromada (territorial community) affected by the conflict and the identification of levers that will facilitate the development of social entrepreneurship initiatives driven by the level of social cohesion in the hromada. Methodology. The survey instrument was structured around five conceptual blocks, each probing distinct aspects of social cohesion: sense of belonging and hromada identity, shared challenges and collective problem-solving, interaction and communication patterns, common social and cultural practices, mutual assistance and support networks. The study sample included 150 residents of Chernihiv hromada. The study used a purposive sampling strategy to ensure representation of different segments of the Chernihiv hromada, with a particular focus on groups relevant to social cohesion and reintegration efforts. The survey results are broken down by components of social cohesion. A significant number of respondents rated their sense of belonging to the hromada as "very important", emphasising the strong collective identity based on the hromada's rich historical heritage. Heritage not only promotes social cohesion, but also creates opportunities for social entrepreneurship, and initiatives such as heritage tourism and traditional crafts bring economic benefits. Collective resilience, especially in the context of post-insurgency recovery, has become a powerful unifying force, reinforcing the social values of collective support. Respondents identified local economic development as a crucial factor, emphasising their commitment to supporting small businesses. The survey also showed that responsible governance plays a vital role in hromada engagement: 80% of participants recognised successful co-operation between citizens and local authorities. Civic engagement and hromada involvement were identified as key pillars of belonging to the hromada (67% of respondents value active participation in hromada affairs). The commitment to inclusive social integration of internally displaced persons and veterans further illustrates the hromada's commitment to social cohesion. Priorities include economic development, infrastructure restoration and security, reflecting the hromada's focus on recovery. Communication patterns indicate a satisfactory level of interaction between residents, and shared cultural practices and mutual support networks are considered vital to strengthening social cohesion. Practical implications. The results of the study can be used for further research and practical application to develop a strategy for the development of social entrepreneurship at all taxonomic levels. Value / Originality. The original approach to developing a strategic framework, which emphasises the interdependence between social cohesion and social entrepreneurship as a tool for reintegrating military personnel, veterans and their families, is based on the study of the components of social cohesion from the perspective of residents, and contributes to the conceptualisation of a social entrepreneurship development strategy.